2008
DOI: 10.1007/s00436-008-1217-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 5-week doxycycline treatment on adult Onchocerca volvulus

Abstract: The effects of 5-week doxycycline treatment on the depletion of Wolbachia endobacteria from Onchocerca volvulus, on the interruption of embryogenesis and on microfilariae production, and with regard to macrofilaricidal activity were studied. In 2003, in an endemic area in Ghana, 22 onchocerciasis patients received 100 mg/day doxycycline for 5 weeks. Two years after the start of the study, 20 treated and ten untreated patients were nodulectomized and skin microfilariae were counted. The onchocercomas were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 32 publications
2
76
0
Order By: Relevance
“…Our observations on ocular MF (MFAC and MFC) strengthen previous examinations of onchocerciasis patients treated repeatedly for less than 10 years [13,14]. Furthermore, the recent application of doxycycline as a macrofi laricidal drug which will eliminate endosymbiontic bacteria of the genus Wolbachia from adult O. volvulus may further strengthen the available onchocerciareview article sis control measures [15]. Th e eff ect of doxycycline treatment on ocular pathology in onchocerciasis should intensely be studied; an accelerated death of MF and adult O. volvulus and rapid disappearance of MFAC and DMFC supported by doxycycline may provide an additional measure for prevention and elimination of O. volvulus infection-associated pathologies in patients.…”
Section: Long-term Consequences Of Ivermectin Treatmentsupporting
confidence: 77%
“…Our observations on ocular MF (MFAC and MFC) strengthen previous examinations of onchocerciasis patients treated repeatedly for less than 10 years [13,14]. Furthermore, the recent application of doxycycline as a macrofi laricidal drug which will eliminate endosymbiontic bacteria of the genus Wolbachia from adult O. volvulus may further strengthen the available onchocerciareview article sis control measures [15]. Th e eff ect of doxycycline treatment on ocular pathology in onchocerciasis should intensely be studied; an accelerated death of MF and adult O. volvulus and rapid disappearance of MFAC and DMFC supported by doxycycline may provide an additional measure for prevention and elimination of O. volvulus infection-associated pathologies in patients.…”
Section: Long-term Consequences Of Ivermectin Treatmentsupporting
confidence: 77%
“…Doxycycline efficacy without IVM had also been observed in the trial using doxycycline at 100 mg/day for 5 weeks (37).…”
mentioning
confidence: 76%
“…This study was terminated too early to allow assessment of a macrofilaricidal effect, which is seen only after approximately 2 years following treatment with doxycycline. Such an effect was, however, observed in further doubleblind, placebo-controlled, randomized trials in Ghana, after administration of 200 mg/day of doxycycline for 4 or 6 weeks or of 100 mg/day for 5 weeks, whereby the highest dose showed a macrofilaricidal effect of up to 60% (70% if worms that had been newly acquired during the observation period were subtracted), in contrast to the 50% (60% after subtraction of newly acquired worms) seen after the 4-week or the 5-week dose (36,37). The female worms that were still alive at the time of nodulectomy (extirpation of the onchocercomata) were sterile.…”
Section: Human Field Trials With Antiwolbachial Drugsmentioning
confidence: 99%
“…We analyzed urine samples from patients with O. volvulus who received either doxycycline or placebo over a 4-to 6-wk period. Sample sets were collected 20 mo after treatment and were shown both to kill the endosymbiont Wolbachia and to sterilize the nematode (16,17). The quantification experiments revealed a significantly reduced concentration of NATOG in doxycycline-treated patients (9.5 ± 1.7 μM) compared with untreated O. volvulus-positive patients (P < 0.001) and placebo-treated patients (33.5 ± 10.7 μM; P = 0.0072).…”
Section: −8mentioning
confidence: 99%
“…The discovery of a specific tyramine receptor in Caenorhabditis elegans infers an importance of this neurotransmitter in nematodes (22). Accordingly, a high level of activity of this decarboxylase was identified in the third-stage larvae of O. volvulus, suggesting a critical role for this neurotransmitter in the worm's development (23), a point in fact that readily justifies the reduced concentration of biomarker NATOG in doxycyclinetreated patients, which leads to the sterilization of adult worms (16,17). Based on literature precedents, we concluded that N-acetylation of tyramine by arylalkylamine N-acetyltransferase (AANAT) is the second metabolic step (24,25) in the biosynthesis of NATOG.…”
Section: −8mentioning
confidence: 99%